TAEGRO (BACILLUS AMYLOLIQUEFACIENS FZB24) IN EUROPEAN PLANT PROTECTION SYSTEMS: A REVIEW OF LITERATURE AND APPLICATION PRACTICES - Ovchinnikova , О.; Aliokhin , В.; Stiurko , М. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The article examines the experience of European farmers in using the biofungicide Taegro for plant protection. Modern agriculture faces challenges related to ensuring effective protection against fungal diseases while reducing the use of chemical pesticides. Increasing environmental requirements, pathogen resistance development, and the need for safe food production encourage the search for alternative plant protection methods. In this context, biofungicides, particularly Taegro, are gaining importance as environmentally friendly alternatives to chemical plant protection products. The study analyzes the advantages of biofungicides over traditional chemical fungicides, including their safety for humans and animals, beneficial effects on soil microbiota, short residual activity, and the ability to be used at various plant growth stages. Taegro is characterized by its resistance to rain and ultraviolet radiation, compatibility with other crop protection products, and systemic action against fungal pathogens. It is effectively used in European countries for protecting berry, vegetable, fruit, and ornamental crops, ensuring a reduction in the incidence of diseases such as gray mold, powdery mildew, and late blight. Field trials in France, Italy, Germany, Poland, and Spain confirm that Taegro can reduce disease prevalence by 40–70 %, depending on the crop and pathogen. The article highlights successful cases of Taegro application in strawberry, raspberry, grapevine, tomato, and ornamental plant production. Additionally, the study addresses the prospects of integrating Taegro into sustainable farming systems and its role in reducing pesticide residues in agricultural products. The findings support the importance of further research on the long-term impact of biofungicides on agroecosystems and the optimization of their application strategies to enhance efficiency and economic feasibility.